Pengembangan Media Alat Bantu Kayang Pembelajaran Senam Lantai - Prasetya, Ary Budhi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to produce a model of media development tools for learninggymnastics floor Kayang in class VIII SMP Negeri 1 Rembang Kragan.The method usedis the development of Borg & Gall. From the test results obtained from the evaluation ofexperts, namely, physical education specialists 82.5% (meets both criteria), 92.5% learningexperts (meet criteria very well). Small-scale trial results 96% (meets the criteria very well),and a large-scale trial of 97.5% (meet criteria very well). Based on the research results, it canbe concluded that this Kayang media tools can be used for learning Penjasorkes in gymnasticsfloor for class VIII SMP Negeri 1 Rembang Kragan.